PENGARUH PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK HOTEL DI KOTA SURAKARTA - Kurniawan, Yohanes Adi Pradana; Pramesti, Hernawati (PRESTASI, 2014)
ABSTRACTÂ The objective of research is to obtain empirical evidence that the Taxpayerâs perception on self-assessment system, taxing apparatus role, and taxpayer awareness partially affect significantly the hotel taxpayer compliance in Surakarta city and to obtain empirical evidence that the Taxpayerâs perception on self-assessment system, taxing apparatus role, and taxpayer awareness simultaneously affect significantly the hotel taxpayer compliance in Surakarta city. Â The sample of research was taken using convenience sampling method, obtaining 40 respondents. Techniques of analyzing data used were validity, reliability, classical assumption, t-, F- and determination coefficient tests.The result of data processing using a multiple regression analysis showed that the measurement using t-test at significance level of 5% found that the Taxpayerâs perception on self-assessment system affected positively and significantly the hotel taxpayer compliance in Surakarta city. Similarly, the role of taxing apparatus evidently affected positively and significantly the hotel taxpayer compliance in Surakarta city. The taxpayer awareness also affected positively and significantly the hotel taxpayer compliance in Surakarta city. Based on the F-test result at significance level of 5%, it could be found that the three variables of Taxpayerâs perception on self-assessment system, taxing apparatus role, and taxpayer awareness simultaneously affected positively and significantly the hotel taxpayer compliance in Surakarta city. Â Keywords: self-assessment, taxing apparatus, awareness, compliance